Eksekusi Jaminan Gadai Emas pada Bank Syariah Indonesia - Agus Setyawan; Sugeng Djatmiko (Syntax Literate, 2023)
Pawn transactions in Islamic jurisprudence are called al rahn. Rahn has many definitions, one of which in Arabic rahn has a permanent and continuous meaning. As for the definition of rahn in sharia terms, the scholars explained with the phrase, "Making property as collateral for debt to be repaid with the guarantee when unable to pay it off." The system of debt and credit transactions with pawns is allowed in Islam because there are arguments from the Qur'an, Sunnah, and ijtihad on which to base. So you don't need to hesitate anymore in sharia pawn transactions. The verse of the Qur'an that can be used as the legal basis for a pawn agreement is Q.S. Al Baqarah verses 282 and 283. Indonesia is one of the countries with the largest Muslim population, this makes Indonesia a potential market for sharia-based financial services. Where this sharia service meets the elements of Islamic law, including Rukun Rahn. faced by society. One of the banks that has service products in the form of pawns is the Indonesian Islamic Bank, hereinafter referred to as BSI. Where BSI runs a pawn service product in accordance with sharia and Islamic law that applies in Indonesia. This pawn is a bank lending money to customers/debtors with collateral, within a certain time and a certain amount of interest, and the debtor has an obligation to pay the loan in accordance with the amount of the price and maturity period that has been determined by the Bank and agreed upon by the debtor. Goods that can be guaranteed objects at BSI include Gold, Precious Metals, House Certificates or Land Certificates, etc.